Pelatihan Pembuatan Olahan Kreatif Berbahan Dasar Labu Siam Pada Ibu-Ibu Kelompok Tani Boritallasa, Desa Rappolemba, Kec. Tompobulu, Kab. Gowa - Hastuti, Hastuti; Marlina, Sitti; Rusdianto, Rusdianto (Lembaga Dongan Dosen, 2025)
Gowa Regency is the highest chayote producing district in South Sulawesi. Rappolemba Village is a center for producing horticultural crops, especially chayote. The high production rate of chayote, especially during harvest, is not directly proportional to market absorption. This condition is certainly a matter of concern because the low selling price is not enough to return the capital spent by farmers. This service aims to increase the knowledge and skills of chayote farmers in creative processing of chayote by making preparations such as chips, pudding and candy. Apart from that, the ladies from the chayote farming group are also provided with knowledge about product branding and marketing both offline and online. This service method is implemented through the stages of planning, socialization, implementation and evaluation. The output that has been obtained from the results of this service is increasing the knowledge and skills of farmer groups in processing chayote into various creative preparations with high selling value, knowledge about branding and marketing products offline and online.